Relationship between Emotional Intelligence, Learning Motivation, and Discipline in Early Childhood - Hikmah Pertiwi; Irma Yuliantina (Journal of Childhood Development, 2024)
This study aims to analyze the relationship between emotional intelligence, learning motivation, and discipline in early childhood at Ikhwanus Shafa Kindergarten. This study uses a quantitative approach with a correlational design to determine the extent to which emotional intelligence and learning motivation affect children's discipline in an early childhood education environment. The research sample consisted of 25 children aged 5-6 years enrolled in Ikhwanus Shafa Kindergarten, with data collection through observation, questionnaires, and structured interviews with teachers and parents. Data analysis was carried out using Pearson correlation statistical techniques to measure the relationship between the variables studied. The results showed that there is a significant positive relationship between emotional intelligence and learning motivation with children's discipline. High emotional intelligence in children contributes to increased learning motivation, which in turn supports the achievement of better discipline. These findings indicate the importance of developing emotional intelligence and learning motivation as determining factors in the formation of disciplinary behaviour in early childhood. The implication of this study is the need for an integrated emotional intelligence development program in the early childhood education curriculum to improve the quality of education and children's character.